IMPORTANCE OF SOFTWARE APPLICATION ‘KAVACH’ - Prajapati, Dhananjay Kantibhai; Sharma, Ravi; Sharma, Varun; Sharma, Atul Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of Kavach is to protect the train from accidents. After seeing so many accidents in the train, Indian Railways implemented an indigenous technology which is called Kavach. Kavach is an indigenously developed automatic train protection (ATP) system. This system has been developed by the Research Design & Standards Organization (RDSO). This cover is the world’s cheapest and indigenous train protection system. This system activates the automatic brake system in the train if the loco pilot stops controlling the train. What I fail to do is that this system automatically controls our trains and it will cost only Rs 50 lakh per kilometer to install this system. While the cost of this system is around Rs 2 crore, if this system is confirmed then this system will be exported all over the world. This technology was tested on 4 March 2022. In which Rail Minister Ashwini Vaishnav was in one locomotive and GM of South-Central Railway in the other locomotive, this test was conducted between Gulgudda and passed Chitgidda railway station. During this test, both the trains came face to face in their scheduled speed. While moving, the Kavach system got activated and automatic brake system got activated in both the locomotives and both the locomotives stopped at a distance of 380 meters. In which jumping the red signal was also tested.